A retrospective analysis of the use of lokivetmab in the management of allergic pruritus in a referral population of 135 dogs in the western USA. Issue 6 (23rd August 2018) - Souza, Clarissa P.; Rosychuk, Rod A. W.; Contreras, Elena T.; Schissler, Jennifer R.; Simpson, Andrew C.
Abstract : Background: Lokivetmab neutralizes IL‐31, a cytokine that plays an important role in the pathogenesis of atopic dermatitis (AD) in dogs. Objective: To review experience of one year of treatment with lokivetmab for the control of pruritus in dogs with allergic dermatitis. Animals: Eighty dogs diagnosed with AD, ten with concurrent adverse food reaction and AD and 45 with allergic dermatitis of undetermined cause. Three dogs were lost to follow‐ up. Methods and materials: Retrospective analysis of medical records of dogs with allergic dermatitis treated with lokivetmab from November 2015 to October 2016. Treatment success for owner‐assessed pruritus was empirically defined as ≥2 cm reduction in Visual Analog Scale (pVAS) from baseline. A ≥50% reduction in pVAS also was recorded. Results: Pruritus improvement was achieved in 116 of 132 dogs (87.8%) following initial lokivetmab administration at 1.8 to 3.7 mg/kg ( P  <   0.001). A pVAS reduction of ≥50% was recorded in 104 dogs (77.0%). Dogs with severe/very severe pruritus prior to treatment and large/giant sized dogs, had 2.7 and 2.8 times higher odds of treatment success, respectively. There were no significant associations between treatment success and age of onset of clinical signs, disease chronicity, lokivetmab dosage or age at initial lokivetmab administration. Dogs that did not previously respond to oclacitinib were less likely to respond to lokivetmab. Adverse effects including lethargy, vomiting, hyperexcitability, pain at injection site and urinary incontinence were reported in 11 of 132 dogs. Conclusions and clinical importance: Lokivetmab at labelled dosages was a fast, safe and efficacious therapy for the control of pruritus in dogs with allergic dermatitis. Abstract : Background – Lokivetmab neutralizes IL‐31, a cytokine that plays an important role in the pathogenesis of atopic dermatitis (AD) in dogs.Objective – To review experience of one year of treatment with lokivetmab for the control of pruritus in dogs with allergic dermatitis.Conclusions and clinical importance – Lokivetmab at labelled dosages was a fast, safe and efficacious therapy for the control of pruritus in dogs with allergic dermatitis.